2018
DOI: 10.1016/j.athoracsur.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Liberal Use of Delayed Sternal Closure in Children Is Not Associated With Increased Morbidity

Abstract: A liberal policy of DSC does not adversely affect surgical outcomes, including infectious complications and length of stay. We submit that need for DSC should not, by itself, be considered a source of morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
0
24
1
Order By: Relevance
“…Twelve studies 3,4,6,7,12,14,18,20,28,30,32,36 made specific mention of obtaining routine mediastinal tissue and/or fluid cultures at the time of definitive chest closure and adjusted antibiotic regimens based on sensitivities in the event of positive cultures. One study 26 obtained cultures at closing only if there was a concern for infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies 3,4,6,7,12,14,18,20,28,30,32,36 made specific mention of obtaining routine mediastinal tissue and/or fluid cultures at the time of definitive chest closure and adjusted antibiotic regimens based on sensitivities in the event of positive cultures. One study 26 obtained cultures at closing only if there was a concern for infection.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative infections were defined by each author. Most studies 3,6 -9,17 -24 used the National Health Safety Network/Centers for Disease Control and Prevention (NHSN/CDC) guidelines, 25 and one study 26 referenced the Society of Thoracic Surgeons Congenital Heart Surgery Database (STS CHSD) definitions. 11 Studies using the NHSN/CDC definitions referenced the 1988 guidelines, 2008 guidelines, or did not specify which guidelines were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of DSC based either on hemodynamic instability in the operating room or more broadly on specific procedure performed and anticipated instability has been studied. 12 Kumar et al 12 found there was no increase in morbidity associated with a policy of planned DSC for complex surgery, especially in neonates, in whom postoperative hemodynamic .525…”
Section: Commentsmentioning
confidence: 99%
“…Often times, these decisions are tempered by the unit's comfort level with deferred sternal closure and their own perception of benefits versus complications. A recent study by Ram Kumar et al [8] analyzed 1000 patients, mostly newborns, who had deferred sternal closure following complex congenital heart repairs. They had a liberal approach to deferring sternal closure, utilizing it almost uniformly for all operations performed under circulatory arrest, or those in Society of Thoracic Surgeons-European Association for Cardio-Thoracic Surgery (STAT) category 4 or 5.…”
mentioning
confidence: 99%